Determination of Dry Matter Content of Eggplant Raw Materials - Yaxshibekovich, Islamov Soxib; Kurvondurdiyevich, Axmedov Shuxrat (American Journal of Botany and Bioengineering, 2024)
in the experiments in this article, the amount of dry matter in the raw materials of varieties and hybrids of eggplant, 4.9% in the variety of Aurora, 4.7% in the variety Surkhan Gozali, 5.2% in Anet F1, 5% in the hybrid Zamin G'1 .0%, 5.1% of Pantera G'1 hybrid and 4.8% of Barcelona G'1 hybrid were found in our experiments.